Promoting Learning and Upskilling for Success (PLUS): An Inclusive Excellence Framework to Facilitate Workplace Readiness of Underrepresented Adult Learners (UALs) - T. Christa Guilbaud; Patrick Guilbaud (Adult Education Research Conference, 2023)
We propose Promoting Learning and Upskilling for Success, an inclusive excellence framework developed to help underrepresented adult learners gain the knowledge and competence needed for the modern workplace.
Keywords: Underrepresented Adult Learners; Learning and Upskilling; Inclusive Excellence Interventions; Workplace Readiness